Unlocking Students’ Creative Thinking in Mathematics: A Study on Three-Dimensional Shapes - Arnisya, Melinda Fahriani; Afriansyah, Ekasatya Aldila (Department of Mathematics Education Program IPI Garut, 2024)
Kemampuan berpikir kreatif perlu dimiliki oleh siswa dalam pembelajaran matematika. Penelitian ini bertujuan untuk menganalisis kemampuab berpikir kreatif siswa SMP pada materi Bangun Ruang Sisi Datar Kubus dan Balok. Metode penelitian ini adalah deskriptif kualitatif. Penentuan subjek penelitian dilakukan secara Purposive Sampling dengan memilih 3 orang siswa kelas VIII. Data diperoleh dengan cara melakukan tes tertulis, wawancara, dan observasi. Setiap data atau informasi yang diperoleh dianalisis dalam bentuk deskriptif. Kemampuan berpikir kreatif yang dimiliki siswa dianalisis berdasarkan indikator-indikator kemampuan berpikir kreatif. Hasil penelitian ini adalah keempat indikator kemampuan berpikir kreatif siswa perlu ditingkatkan karena belum optimal. Faktor-faktor yang mempengaruhi kemampuan berpikir kreatif yaitu proses pembelajaran, pemahaman siswa, serta pemberian latihan soal. Creative thinking skills are essential for students in learning mathematics. This study aims to analyze the creative thinking abilities of junior high school students in the topic of Three-Dimensional Shapes, specifically cubes and rectangular prisms. The research method used is qualitative descriptive. The selection of research subjects was conducted using purposive sampling, involving three eighth-grade students. Data were collected through written tests, interviews, and observations. All obtained data or information were analyzed descriptively. Students' creative thinking skills were analyzed based on specific indicators of creative thinking ability. The results of this study show that all four indicators of students' creative thinking skills need improvement, as they are not yet optimal. Factors influencing creative thinking skills include the learning process, students' comprehension, and the provision of practice problems.